Mechanochemical reactivity inhibited, prohibited and reversed by liquid additives: examples from crystal-form screens. Issue 9 (20th January 2021) - Arhangelskis, Mihails; Bučar, Dejan-Krešimir; Bordignon, Simone; Chierotti, Michele R.; Stratford, Samuel A.; Voinovich, Dario; Jones, William; Hasa, Dritan
Abstract : Liquid additives can exert catalytic, inhibitive or prohibitive effects on the mechanochemical formation of multi-component molecular crystals. Abstract : We demonstrate that liquid additives can exert inhibitive or prohibitive effects on the mechanochemical formation of multi-component molecular crystals, and report that certain additives unexpectedly prompt the dismantling of such solids into physical mixtures of their constituents. Computational methods were employed in an attempt to identify possible reasons for these previously unrecognised effects of liquid additives on mechanochemical transformations.